SYNTHESIS AND BIOLOGICAL STUDIES OF TRIHYDRO PYRIDO [2, 3-D] PYRIMIDINES 6 –CARBONITRILE: Life Sciences-Organic Chemistry - CHAUDHARI, PARTHIV. K; S, Author (International Journal of Life Science and Pharma Research, 2011)
The synthesis of 5-amino-4-aryl-7-oxo-2-mercato-4,8,4a-trihydro pyrido [2,3-d]pyrimidines-6-carbonitrile (VIIIa-m) have been undertaken by the condensation of 4-amino -5-cyano-6-aryl-2-mercato-5,6-dihydro pyrimidines with ethylcyanoacetate. The constitution of the products has been delineated by elemental analyses IR, PMR and mass spectral data.